The Impact of Sustainability Reports on The Profitability of Companies In The Primary Consumer Goods Sector Listed on The IDX For The Period - Nurul Asma Rani; Hariany Idris; Azwar Anwar (SIMAK, 2026)
This study aims to examine the effect of sustainability reporting on the profitability of primary consumer goods companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Sustainability reporting is measured using the Sustainability Report Disclosure Index (SRDI) based on the Global Reporting Initiative (GRI) Standards, while profitability is measured by Return on Assets (ROA). The sample was selected using purposive sampling, resulting in 68 observations, and analyzed using simple linear regression. The results indicate that sustainability reporting has a significant negative effect on profitability of companies in the primary consumer goods industry, suggesting that increased disclosure tends to reduce ROA in the short term. This study is limited by the quantitative measurement of SRDI, the use of ROA as the sole profitability indicator, and the relatively short observation period.